Pengaruh Pelaksanaan Kegiatan Ekstrakurikular Pramuka Terhadap Pendidikan Karakter Siswa di SDN 060826 Kecamatan Medan Area - Rizka Fadhilah Priono; Juni Mellyani Hasibuan; Zulhijjah Febriyani Sitepu; Maria Grasella Silaban; Fajar Siddik Siregar (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The aim of this research is to analyze the influence of scout extracurricular activities in elementary schools on students' personality development. The research method used is a qualitative approach using data collection techniques of in-depth interviews, participatory observation and document analysis. The research population consisted of elementary school students, teachers, and scout leaders. Research shows that scouting activities have an important role in developing student character. This activity not only increases students' discipline, responsibility and independence, but also forms social attitudes, cooperation, and strengthens leadership abilities and self-confidence. These results indicate that scouting activities can be an effective means for character education in elementary schools.